Developmental and attachment-based perspectives on dissociation: beyond the effects of maltreatment. Issue 1 (31st December 2020) - Guérin-Marion, Camille; Sezlik, Sage; Bureau, Jean-François
ABSTRACT: Background: Numerous years of theory and research have informed our understanding of the caregiving experiences that confer vulnerability for dissociation. This work has resulted in widespread agreement on the role of childhood maltreatment as an aetiological factor. Objective: With clear integration of this perspective, the current paper draws attention to the spectrum of vulnerability that can exist over and above the trauma of maltreatment within early caregiving experiences. Method: An integrative review of the developmental literature on dissociation is presented. Results: We first review and integrate existing developmental theories of dissociation into a more unified perspective, highlighting a combination of defensive and intersubjective pathways towards dissociative outcomes. Next, we present empirical research demonstrating which specific caregiving experiences are associated with dissociation. Lastly, we review recent neurodevelopmental research demonstrating that (non-extreme) caregiving stressors during infancy impact the developing limbic structures in the brain. We conclude by offering directions for future research. Conclusion: Findings make the case for approaching assessments of the caregiver-child relationship with discernment of factors beyond the presence/absence of maltreatment when conceptualizing risk pathways toward dissociation. Abstract : HIGHLIGHTS: Dissociation develops from infancy in the context of stressors in the caregiver-child relationship. These stressors canoccur with, but also without maltreatment. Changes in limbic brain regions may partly explain why such early stressors increase risk for dissociation.